Increase in Polyphenolic Substances from Fermented Robusta Coffee Pulp (Coffea canephora L.) by Using Indigenous Actinomycetes - Eka Putri; Yaya Rukayadi; Titi Candra Sunarti; Anja Meryandini (Bogor Agricultural University, Indonesia, 2023)
The fermentation of the coffee fruit processing into coffee beans leaves the fermented coffee pulp which still contains polyphenol secondary metabolites. This study aimed to analyze the total flavonoid content (TFC) and total phenolic content (TPC) of fermented robusta coffee pulp (Coffea canephora L.) by using indigenous Actinomycetes. The ability of fermented extracts to inhibit free radical DPPH (2,2-diphenyl-1-picrylhydrazyl) also were done. In this study, coffee cherries were fermented in the solid-state fermentation cultivation (SSF) using isolates HJ4.5b, P2b(b).3 and P2b(b).18 which in previous studies were reported to have cellulolytic and xylanolytic activities. Determination of molecular identification base on 16S rRNA gen showed the isolates HJ4.5b and P2b(b).3 have similarities to the genus Streptomycetes, while P2b(b).18 has a homologous base arrangement with a rare actinomycetes genus Micromonospora. Fermentation using P2b(b).3 on the 9th day of fermentation indicated the highest percentage increase in TFC (295.54%) with IC50 18.41 µl/ml and having an antioxidant activity index (AAI) value of 2.14 which was included in the very strong antioxidant activity category.